Book Reviews. Issue 1 (1st March 2019) - Silver, Hilary; et al.,
Abstract : Rafaela Dancygier, Dilemmas of Inclusion: Muslims in European Politics (Princeton: Princeton University Press, 2017) Reviewed by Hilary Silver, Sociology, George Washington University Thomas Großbölting, Losing Heaven: Religion in Germany since 1945; translated by Alex Skinner (New York: Berghahn Books, 2017. Reviewed by Jeffrey Luppes, World Languages, Indiana University South Bend Hans Vorländer, Maik Herold, and Steven Schäller, PEGIDA and New Right-Wing Populism In Germany (London: Palgrave Macmillan, 2018) Reviewed by Joyce Mushaben, Political Science, University of Missouri St. Louis Kara L. Ritzheimer, "Trash, " Censorship, and National Identity in Early Twentieth-Century Germany (Cambridge: Cambridge University Press, 2016) Reviewed by Ambika Natarajan, History, Philosophy, and Religion, Oregon State University Anna Saunders, Memorializing the GDR: Monuments and Memory After 1989 (New York: Berghahn Books, 2018) Reviewed by Jeffrey Luppes, World Languages, Indiana University South Bend Desmond Dinan, Neill Nugent and William E. Paterson, eds., The European Union in Crisis (London: Palgrave, 2017) Reviewed by Helge F. Jani, Hamburg, Germany Noah Benezra Strote, Lions and Lambs: Conflict in Weimar and the Creation of Post-Nazi Germany (New Haven: Yale University Press, 2017). Reviewed by Darren O'Byrne, History, University of Cambridge Chunjie Zhang, Transculturality and German Discourse in the Age of European Colonialism (Evanston: Northwestern University Press, 2017) Reviewed by Christopher Thomas Goodwin, History, University of Illinois, Urbana-Champaign Marcel Fratzscher, The Germany Illusion: Between Economic Euphoria and Despair (Oxford: Oxford University Press, 2018). Reviewed by Stephen J. Silvia, International Relations, American University